Susceptibility of Candida albicans and Candida glabrata biofilms to silver nanoparticles in intermediate and mature development phases - Monteiro, Douglas Roberto [UNESP]; Takamiya, Aline Satie [UNESP]; Feresin, Leonardo Perina [UNESP]; Gorup, Luiz Fernando; Camargo, Emerson Rodrigues de; Botazzo Delbem, Alberto Carlos [UNESP]; Henriques, Mariana; Barbosa, Debora Barros [UNESP] (Elsevier B.V., 2015)
Purpose: The aim of this study was to investigate the susceptibility of Candida albicans and Candida glabrata biofilm development, in their intermediate and maturation stages, to the influence of silver nanoparticles (SN). Methods: SN (5 nm) suspensions were synthesized via reduction of silver nitrate by a solution of sodium citrate. These suspensions were used to treat Candida biofilms for five hours, grown on acrylic surfaces for 24-h (intermediate stage) and 48-h (maturation stage), and their efficacy was determined by total biomass (using crystal violet staining) and colony forming units (CFUs) quantification. Results: SN promoted significant reductions (p < 0.05) in the total biomass and number of CPUs of Candida biofilms, ranging from 23% to 51.5% and 0.63 to 1.59-log(10), respectively. Moreover, there were no significant differences in the total biofilm biomass (p > 0.05), when the different stages of biofilm development (24 or 48 h) were exposed to SN. Comparing the number of CFUs between 24- and 48-h biofilms treated with SN, a significant difference (p < 0.05) was found only for the C. albicans 324LA/94 strain. Conclusions: In general, the intermediate and maturation stages of biofilm development do not interfere in the susceptibility of C. albicans and C. glabrata biofilms to SN. These findings are fundamental for the deployment of new therapies aimed at preventing denture stomatitis. (C) 2014 Japan Prosthodontic Society. Published by Elsevier Ireland. All rights reserved.
Keywords: Silver nanoparticles; Denture stomatitis; Biofilms; Candida albicans; Candida glabrata